Synthesis, structural, thermal, mechanical, and nano-scale free volume properties of novel PbO/PVC/PMMA nanocomposites. (7th October 2020) - El-Gamal, S.; Elsayed, M.
Abstract: Novel nanocomposite films (PbO/PVC/PMMA) were prepared by solution casting. The influence of PbO loading, from 0.5 to 4 wt%, on the structural, thermal, mechanical, and free volume properties of the PVC/PMMA blend was reported. The structural results showed that the average crystallite size of PbO is 47.8 nm and it had nanoparticles morphology with average size, 46.3 nm as confirmed by HR-TEM. Loading PbO appeared new crystalline peaks attributable to α-PbO and increased the blend amorphicity. The blend had a smooth surface with fingerprint shape, which confirmed the miscibility between PVC & PMMA while PbO loading increased the surface roughness. Good distribution was reported to 2 wt% PbO loading. Thermogravimetric analysis (TGA) revealed an increase in the thermal stability of PNCs films. Higher storage moduli of PNCs films were reported as revealed from Dynamic Mechanical Analysis (DMA) results besides the increase in T g with loading which confirmed the interaction between PbO & blend and enable PNCs to have better mechanical properties. Positron annihilation lifetime spectroscopy (PALS) measurements manifested a decrease in the ortho-positronium pick off lifetime (τ3 ) and the free volume (VF ) with loading. This is due to the reduction in the size of free volume holes in regions near PbO, the polar groups in the blend matrix, and the hole-filling mechanism. τ3 & VF increased with heating due to the thermal expansion of the free volume holes within the PVC/PMMA matrix. As the main result of this work, PbO formed small free-volume structures within the PVC/PMMA matrix, which lead to the superior thermal and mechanical properties of nanocomposite films that could widen the blend applications. Graphical abstract: Image 1 Highlights: Novel polymer nanocomposites (PbO/PVC/PMMA), were prepared by solution casting. The structural, thermal, mechanical, and free volume properties of PNCs were studied. An enhancement in the thermal stability of PbO/PVC/PMMA films was reported. Higher storage moduli of PbO/PVC/PMMA films were reported compared to blend. PbO formed small free-volume structures within blend leading to superior properties.